2008
DOI: 10.1038/ng.241
|View full text |Cite
|
Sign up to set email alerts
|

EYS, encoding an ortholog of Drosophila spacemaker, is mutated in autosomal recessive retinitis pigmentosa

Abstract: Using a positional cloning approach supported by comparative genomics, we have identified a previously unreported gene, EYS, at the RP25 locus on chromosome 6q12 commonly mutated in autosomal recessive retinitis pigmentosa. Spanning over 2 Mb, this is the largest eye-specific gene identified so far. EYS is independently disrupted in four other mammalian lineages, including that of rodents, but is well conserved from Drosophila to man and is likely to have a role in the modeling of retinal architecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
178
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(196 citation statements)
references
References 13 publications
9
178
3
Order By: Relevance
“…1-3 CRD can manifest under a variety of inheritance models, though the autosomal recessive mode of inheritance is the most prevalent. To date, eight genes responsible for autosomal recessive CRD have been identified: ABCA4 (OMIM#601691), 4 ADAM9 (OMIM#602713), 5 C8orf37 (OMIM#614477), 6 CERKL (OMIM#608381), 7 EYS (OMIM#612424), 8 RPGRIP1 (OMIM#605446), 9 RAB28 (OMIM#612994) 10 and TULP1 (OMIM#602280). 11 However, the known variants do not account for all cases of CRD.…”
Section: Introductionmentioning
confidence: 99%
“…1-3 CRD can manifest under a variety of inheritance models, though the autosomal recessive mode of inheritance is the most prevalent. To date, eight genes responsible for autosomal recessive CRD have been identified: ABCA4 (OMIM#601691), 4 ADAM9 (OMIM#602713), 5 C8orf37 (OMIM#614477), 6 CERKL (OMIM#608381), 7 EYS (OMIM#612424), 8 RPGRIP1 (OMIM#605446), 9 RAB28 (OMIM#612994) 10 and TULP1 (OMIM#602280). 11 However, the known variants do not account for all cases of CRD.…”
Section: Introductionmentioning
confidence: 99%
“…In Table 1 we list the 44 currently known genes underlying nonsyndromic recessive retinal dystrophies in human. Mouse orthologs are known for each of these genes, except eyes shut homolog (EYS) (19). Naturally occurring or man-made…”
Section: Animal Models For Recessive Retinal Dystrophiesmentioning
confidence: 99%
“…23,37,38 Truncating variants within the EYS gene (OMIM 612424) were initially associated with arRP in 2008. 39,40 Novel truncating variants were identified in a patient with a clinical diagnosis of autosomal-recessive CRD. 41 Parental testing confirmed that these variants were in trans.…”
Section: Advantages Of Mps Testing Expanding Clinical Phenotypesmentioning
confidence: 99%